The Digitization of Neurodiversity: Real Cyborgs and Virtual Bodies - Isla Ng (Atlantis)
Abstract Motivated by cultural associations between neurodiversity and digital technology, this paper explores digital identity politics by considering the online experiences of people with mental disabilities. I argue that the Internet, even while it provides opportunities for the production of powerful digital feminist counterpublics, can reify the ideological disembodiment and devaluation of identity. This, I argue, limits the Internet’s ability to represent and support disability identities, as well as other forms of identity. I call for the centering of disability theory in digital feminist thought as a way of promoting intersectionality and providing new theoretical methods.